A 0.69-mW Subsampling NB-IoT Receiver Employing a Linearized Q-Boosted LNA - Hongyu Lu; Ahmed Gharib Gadelkarim; Jiannan Huang; Patrick P. Mercier (IEEE Open Journal of the Solid-State Circuits Society)
This article presents a receiver for narrowband IoT (NB-IoT) that eliminates the need for an RF local oscillator (LO) via a subsampling architecture. A pseudo-balun Q-boosted LNA provides sharp anti-aliasing filtering with a noise figure (NF) of 5.6 dB. A direct-coupling derivative superposition technique where low- $V_{t}$ and thick-gate transistors with opposite nonlinear characteristics are combined to improve the measured IIP3 by 7 dB to −18 dBm with little NF overhead. Fabricated in 65-nm CMOS, the entire receiver, including the LNA, an S/H circuit, and a 10-bit SAR ADC, consumes only 0.69 mW while meeting NB-IoT specifications.